2013
DOI: 10.1136/bmjopen-2012-002036
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of prescribing errors in patients admitted to nine hospitals across North West England

Abstract: ObjectiveTo evaluate the prevalence, type and severity of prescribing errors observed between grades of prescriber, ward area, admission or discharge and type of medication prescribed.DesignWard-based clinical pharmacists prospectively documented prescribing errors at the point of clinically checking admission or discharge prescriptions. Error categories and severities were assigned at the point of data collection, and verified independently by the study team.SettingProspective study of nine diverse National H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 22 publications
9
55
2
4
Order By: Relevance
“…Overall clinical pharmacists made interventions in almost 1 in 6 prescribed medications (16.1% of prescribed items) and more than 60% of the interventions were of at least moderate impact. Medication errors were found in 6.8% of all prescribed items, which is slightly lower than the 8.9% rate identified by the EQUIP study [25] which specifically examined prescribing error rates by medical staff in multi-site acute hospitals in the UK. …”
mentioning
confidence: 88%
“…Overall clinical pharmacists made interventions in almost 1 in 6 prescribed medications (16.1% of prescribed items) and more than 60% of the interventions were of at least moderate impact. Medication errors were found in 6.8% of all prescribed items, which is slightly lower than the 8.9% rate identified by the EQUIP study [25] which specifically examined prescribing error rates by medical staff in multi-site acute hospitals in the UK. …”
mentioning
confidence: 88%
“…Study by Kuo et al, reported that 70% prescribing errors was observed among United States America (USA) family physicians while study conducted at West England reported that 43.8% prescriptions contain one or more prescribing errors [7,8]. Study carried out at Nasik, India reported that out of 300 prescriptions 279 prescriptions (93%) were irrational based on the use of essential drug WHO and standard treatment guidelines [9].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the best intentions of healthcare providers and medical staff, things often go wrong, with evidence that approximately 10% of patients suffer an adverse incident related to healthcare interventions Vincent et al 2001), and that over 40% of medication orders contain errors (Seden et al 2013). Not all adverse events and errors are serious, but some are catastrophic, leading to permanent harm or death.…”
Section: Introductionmentioning
confidence: 99%